Scientific Writing Best Practice Training Improves Indonesian Students’ Publication Competence - Johan Setiawan; Dedy Subandowo; Fauzi Rachman; Laurensius Jesen Prasetyo; Muhammad Bagas Dinanta (Carmin: Journal of Community Service, 2026)
This article aims to examine the effectiveness of a best practice–based training program on scientific writing and publication in improving the competencies of Indonesian students at Universiti Malaya. This activity is a form of community service (PkM) with participatory training methods and intensive mentoring involving 30 students. This study used a quantitative pre-experimental approach with a one-group pretest-posttest design. The activity stages include needs analysis, scientific article writing training, mentoring in scientific article writing, and evaluation of training results. Data were collected through scientific writing competency tests and publication readiness questionnaires before and after the training, then analyzed using descriptive statistics and paired sample t-tests. The results of the community service showed a significant increase in writing competency and understanding of the publication process, with an average pretest score of 54.20 increasing to 78.65 in the posttest (p < 0.05). Students experienced improvements in structuring articles, improving the quality of argumentation, applying appropriate citation techniques, and understanding journal selection, submission procedures, and the peer review process. In addition to cognitive aspects, students' readiness and confidence in reading scientific publications also improved. Overall, best-practice-based training proved effective in improving students' academic readiness to produce publishable scientific articles that meet the standards of reputable journals.